2010
DOI: 10.1016/s1734-1140(10)70389-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethylene glycol ethers on cell viability in the human neuroblastoma SH-SY5Y cell line

Abstract: Ethylene glycol ethers (EGEs) are a class of chemicals used extensively in the manufacture of a wide range of domestic and industrial products, which may result in human exposure and toxicity. Hematologic and reproductive toxicity of EGEs are well known whereas their action on neuronal cell viability has not been studied so far. In the present study, we investigated the effects of some EGEs on cell viability and on the hydrogen peroxide-induced damage in the human neuroblastoma (SH-SY5Y) cells. It has been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…BE and PHE affected the total antioxidant activity and lipid peroxidation, whereas the most hydrophilic compound—EE showed no such action. The finding that the adverse effects of EGEs on brain cells depends mainly on their lipophilicity is in line with our previous in vitro study, which showed that PHE, BE and IPE much more strongly damaged human neuroblastoma cell line (SH-SY5Y cells) than the hydrophilic EGEs did (Regulska et al 2010). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…BE and PHE affected the total antioxidant activity and lipid peroxidation, whereas the most hydrophilic compound—EE showed no such action. The finding that the adverse effects of EGEs on brain cells depends mainly on their lipophilicity is in line with our previous in vitro study, which showed that PHE, BE and IPE much more strongly damaged human neuroblastoma cell line (SH-SY5Y cells) than the hydrophilic EGEs did (Regulska et al 2010). …”
Section: Discussionsupporting
confidence: 90%
“…Previously in in vitro experiments we found that BE, PHE and IPE more severely than ME or EE damaged human neuroblastoma cells (SH-SY5Y). Those experiments indicated that more lipophilic EGEs like BE or PHE are more harmful to neurons than those EGEs with higher hydrophilic properties (Regulska et al 2010). In the next experiment, we showed that also in vivo a mixture of two EGEs induced adverse reactions in the brain by decreasing the total antioxidant capacity, enhancing lipid peroxidation and increasing caspase-3 activity in the rat hippocampus and frontal cortex (Pomierny et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the addition of hydrogen peroxide to the cell medium, as a source of detrimental reactive oxygen species, is a well-validated and frequently used model for oxidative stress [18][19][20]. As in our previous experiments, the addition of 0.5 mM H 2 O 2 en- hanced LDH release from the cytosol to the medium and decreased activity of mitochondria dehydrogenase enzymes [20,21]. Cell death induced by hydrogen peroxide is thought to progress mainly via the necrotic mechanism, thus demonstrating that B. monnieri weakened the effect of this toxic factor, the evidence of which is in its neuroprotective effect.…”
mentioning
confidence: 63%
“…Cell viability was measured, as described previously in Ref. [21], by determining the cellular reducing capacity, estimated through the extent of MTT reduction to the insoluble intracellular formazan, which depends on the activity of intracellular dehydrogenases and is independent of changes in the integrity of the plasma membrane. Briefly, culture medium was removed and SH-SY5Y cells were incubated with MTT for 3 h at 37°C.…”
Section: -[45-dimethylthiazol-2-yl]25-diphenyltetrazolium Bromide mentioning
confidence: 99%
“…As a cosmetic preservative, PE is allowable at a maximum authorized concentration of 1% in EU countries, United States, Japan, and Korea. Toxicological data pertaining to the safety evaluation of PE have been summarized [5], and the hazard potential for neurotoxicity and adverse effects on the central nervous system (CNS) remains to be elucidated [6][7][8]. Concerning the CNS health risk, the U.S. Food and Drug Administration (FDA) announced a warning against using a cream product containing PE intended for nursing mothers to help soothe and heal dry or cracked nipples [9].…”
Section: Introductionmentioning
confidence: 99%